The Influence of Information Quality and Functionality on Intention to Use Mobile Apps with Perceived Usefulness as an Intervening Variable - Cahyani, Made Gita Dwi; Dewi, Citra Kusuma; Widodo, Arry; Rubiyanti, Nurafni; Silvianita, Anita (East Asian Journal of Multidisciplinary Research, 2024)
People's behavior towards the internet creates new habits in obtaining easy transactions for purchasing goods and services, such as purchasing plane tickets using online applications. Traveloka is ranked 1st in Online Travel Agent in Indonesia. This research aims to determine the influence of Information Quality and functionality on the Intention to use Traveloka mobile apps with Perceived usefulness as an intervening variable. The population in this research is Traveloka users in Indonesia. The sample in this study has criteria, namely Traveloka users. This research uses quantitative methods with the Smart-PLS analysis technique